IMPROVING THE METHODOLOGY OF DEVELOPING STUDENTS' BASIC COMPETENCE BASED ON INNOVATIVE COOPERATION - Yarova Sevara Boxodir kizi (Western European Studies, 2024)
In the modern education system, the development of basic competence of students is of great importance. This process can be implemented on the basis of innovative cooperation, that is, the quality of education can be improved by using new pedagogical technologies and methods
Keywords: Core competency; Innovative collaboration; Competency approach